MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH DENGAN MENGGUNAKAN MEDIA KARTU BERGAMBAR PADA ANAK USIA DINI - Lestari, Srimpiani (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This research aims to see how the reading skills of the students in Group Learning (KB) Irsyadul Ulum Al-Washliyah Aek Kanopan concerning hijaiyah letters before and after using picture card media. The research design used is classroom action research (CAR) with 20 students from class B as subjects. Data collection in this study is done through observation, oral tests, and documentation in each cycle with the application of playing methods and letter card media, analyzed using descriptive qualitative. The results obtained from the research indicate that students' ability to read hijaiyah letters can be improved through picture card media, as evidenced by the results of three cycles conducted by the researcher. The level of student ability in the pre-cycle was 10% in the fluent category, 20% in the moderate category, while the poor category was 70%. Meanwhile, the results of the first cycle after using picture card media showed that 80% of students were in the fluent category, 10% in the moderate category, and 10% in the poor category. Using picture card media will make it more interesting for students to want to learn to read hijaiyah letters.